2014
DOI: 10.1021/cm502687p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of CuInS2 Colloidal Nanocrystals, Tight Binding of L-Type Ligands

Abstract: We analyze the surface chemistry of CuInS 2 nanocrystals synthesized in the presence of amines. Using solution NMR spectroscopy and elemental analysis, we come to the conclusion that as-synthesized CuInS 2 nanocrystals have charge neutral inorganic cores and are stabilized by a layer of tightly bound L-type amines. In situ NMR heating-up experiments show that desorption of amines can be induced by increasing the temperature, which makes the partial exchange of amines for thiols possible. On the other hand, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 57 publications
6
99
1
1
Order By: Relevance
“…57 However, it was repeatedly reported that Cu-based NCs typically have tightly bound amines bound to the surface. 13,58 It should however be noted that OLA is quite easily desorbed during purification suggesting only a moderate binding affinity for the NC surface, in line with L-type ligand behaviour. To facilitate charge transport/transfer, CASe NCs were thoroughly purified by multiple precipitation/re-dispersion steps and subsequently treated with NH 4 SCN, which could efficiently displace remaining OLA.…”
Section: Resultsmentioning
confidence: 88%
“…57 However, it was repeatedly reported that Cu-based NCs typically have tightly bound amines bound to the surface. 13,58 It should however be noted that OLA is quite easily desorbed during purification suggesting only a moderate binding affinity for the NC surface, in line with L-type ligand behaviour. To facilitate charge transport/transfer, CASe NCs were thoroughly purified by multiple precipitation/re-dispersion steps and subsequently treated with NH 4 SCN, which could efficiently displace remaining OLA.…”
Section: Resultsmentioning
confidence: 88%
“…In apolar solvents,they coordinate to surface metal ions of stoichiometric NCs to yield overall charge-neutral objects. [5] Z-type ligands are neutral electron-pair acceptors (e.g., metal carboxylates) that bind to the surface anions of stoichiometric NCs. [1a] In NC surface chemistry,X-type ligands are presented as negatively charged ligands (RCOO À ,O H À ,C l À )t hat bind to excess surface cations of nonstoichiometric NCs.…”
mentioning
confidence: 99%
“…In the case of CIS NCs, which are stabilized by OlAm after synthesis [21], addition of both NaHSe and (N 2 H 5 ) 2 Se to a polar phase in contact with the original apolar CIS dispersion leads to the transfer of the CIS NCs to the polar phase (see inset Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…As precursors, we focus on CuInS 2 (CIS) nanocrystals (NCs) synthesized by pyrolysis of metal organic precursors in an apolar solvent [21]. Similar NCs have been used before for the formation of CIGS solar cells by a process involving gas-phase selenization and yielding conversion efficiencies of up to 12% [22].…”
Section: Introductionmentioning
confidence: 99%